Calcium‐binding protein EhCaBP3 is recruited to the phagocytic complex of Entamoeba histolytica by interacting with Arp2/3 complex subunit 2. (7th September 2018) - Babuta, Mrigya; Kumar, Sanjeev; Gourinath, Samudrala; Bhattacharya, Sudha; Bhattacharya, Alok
Abstract: Phagocytosis is involved in invasive disease of the parasite Entamoeba histolytica . Upon binding of red blood cells, there is a sequential recruitment of EhC2PK, EhCaBP1, EhAK1, and Arp2/3 complex during the initiation phase. In addition, EhCaBP3 is also recruited to the site and, along with myosin 1B, is thought to be involved in progression of phagocytic cups from initiation to phagosome formation. However, it is not clear how EhCaBP3 gets recruited to the rest of the phagocytic machinery. Here, we show that EhARPC2, a subunit of Arp2/3 complex, interacts with EhCaBP3 in a Ca 2+ ‐dependent manner both in vivo and in vitro. Imaging and pull down experiments suggest that interaction with EhARPC2 is required for the closure of cups and formation of phagosomes. Moreover, downregulation of EhARPC2 prevents localisation of EhCaBP3 to phagocytic cups, suggesting that EhCaBP3 is part of EhC2PK‐EhCaBP1‐EhAK1‐Arp2/3 complex (EhARPC1) pathway. In conclusion, these results suggest that the EhCaBP3–EhARPC2 interaction helps to recruit EhCaBP3 along with myosin 1B to the phagocytic machinery that plays an indispensable role in E. histolytica phagocytosis.